A CMO / SO / BVO photoanode and its preparation method and application
By introducing SiO2 and CoMoO4 layers into the photoanode, the CMO/SO/BVO photoanode is formed, which solves the problems of rapid photogenerated carrier recombination and low light utilization rate, and significantly improves the photoelectrocatalytic water decomposition performance.
Patent Information
- Application Number
- CN202411988483.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing photoanodes have problems of rapid photogenerated carrier recombination and low light utilization, which hinders its further application in photoelectro-catalyzed water decomposition and hydrogen production.
Using the preparation method of CMO/SO/BVO photoanode, a BiOI film is electrodeposited on the substrate material, converted into a BiVO4 film, and a SiO2 intermediate layer and a CoMoO4 layer are formed thereon to form a ternary photoanode.
The photocurrent density and charge separation efficiency are significantly improved, and the photoelectrocatalytic water decomposition performance is improved, so that the CMO/SO/BVO photoanode shows better photoelectrochemical performance under 1.23V vs. RHE conditions.
Smart Images

Figure CN119776893A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photoelectrochemical technology, and in particular to a CMO / SO / BVO photoanode and a preparation method and application thereof. Background Art
[0002] The use of solar-driven photocatalytic water decomposition to produce hydrogen can effectively alleviate the pressure brought to human society by energy crisis and environmental problems. 2 、ZnO、WO 3 、BiVO 4 and Fe 2 O 3 etc. have been widely used in the study of photoelectrochemical water splitting. Among them, BVO, as an n-type semiconductor material, has become a popular candidate material for photoanode due to its suitable energy band position that can meet the oxidation of water and the utilization and absorption of visible light. Unfortunately, the single photoanode has problems such as rapid recombination of photogenerated carriers and low light utilization, which seriously hinders its further application. Loading oxygen evolution co-catalysts is widely considered to be an extremely effective method to improve the efficiency of photoelectrocatalysis. By introducing such co-catalysts, the overpotential of oxygen evolution reaction can be significantly reduced, the reaction kinetics can be accelerated, and thus the overall performance and energy conversion efficiency of the photoelectrocatalytic system can be significantly improved. The close contact interface of the binary photoanode is crucial to improve the separation of photogenerated electrons and holes and enhance the photoelectrocatalytic activity. However, the lattice structures of different materials are quite different, and direct contact between BVO and CMO may lead to unnecessary recombination of photogenerated carriers. In the ternary photoanode system, the oxide as an intermediate layer for carrier migration can promote charge transfer, thereby improving the performance of photoelectrocatalytic water splitting. Therefore, a new photoanode is urgently needed. Summary of the invention
[0003] In order to solve the above technical problems, the purpose of the present invention is to provide a CMO / SO / BVO photoanode and a preparation method and application thereof, so as to solve the problem of poor photoelectrochemical performance of the photoanode in the prior art.
[0004] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing a CMO / SO / BVO photoanode is provided, which comprises the following steps in sequence:
[0005] (1) Electrodepositing a BiOI film on a substrate, cleaning and drying, then drop-coating a dimethyl sulfoxide solution of vanadium acetylacetonate, calcining, cooling, and secondary cleaning to obtain BiVO 4 Thin film, i.e. BVO electrode;
[0006] (2) placing the BVO electrode obtained in step (1) in a NaOH solution of tetraethyl orthosilicate, leaving it to stand, washing it, and drying it to obtain SiO 2The middle layer, i.e., the SO / BVO electrode;
[0007] (3) Place the SO / BVO electrode prepared in step (2) on the CoMoO 4 In the precursor solution, hydrothermal reaction, washing, calcination, CoMoO 4 / SiO 2 / BiVO 4 Photoanode, namely CMO / SO / BVO photoanode.
[0008] On the basis of the above technical solution, the present invention can also be improved as follows:
[0009] Furthermore, in step (1), the substrate material is FTO glass.
[0010] Furthermore, in step (1), the electrodeposition of the BiOI film is carried out in a three-electrode system, wherein the counter electrode is a platinum electrode, the reference electrode is a silver-silver chloride electrode, and the working electrode is a cleaned FTO glass.
[0011] Furthermore, in step (1), the electrodeposition is performed using a constant potential deposition method.
[0012] Furthermore, in step (1), the electrodeposition conditions are: deposition voltage is -0.1 V vs. Ag / AgCl, and deposition time is 300 s.
[0013] Further, in step (1), the electrodeposition solution for electrodepositing the BiOI film is prepared by the following method: Bi(NO 3 ) 3 ·5H 2 O is dissolved in KI solution, the pH value is adjusted to 1-2, and then p-benzoquinone ethanol solution is added and mixed to prepare an electrodeposition solution.
[0014] Furthermore, the concentration of KI solution is 0.3-0.5 mol / L, the concentration of benzoquinone ethanol solution is 0.2-0.3 mol / L, and the concentration of Bi(NO 3 ) 3 ·5H 2 The molar volume ratio of O, KI solution and ethanol solution of p-benzoquinone is 0.02-0.06 mol:45-55 mL:18-22 mL.
[0015] Furthermore, in step (1), the concentration of the dimethyl sulfoxide solution of vanadium acetylacetonate is 0.1-0.3 mol / L.
[0016] Furthermore, in step (1), calcination is performed at 400-500° C. for 1.5-2.5 h.
[0017] Furthermore, in step (1), the heating rate of calcination is 1.5-2.5°C / min.
[0018] Furthermore, in step (1), a secondary cleaning is performed using a 0.8-1.2 mol / L NaOH solution.
[0019] Furthermore, in step (2), the concentration of the NaOH solution of tetraethyl orthosilicate is 0.03-0.07 mol / L.
[0020] The beneficial effect of adopting the above further technical solution is that by improving the preparation process and optimizing the experimental scheme, the production cost of the BVO thin film can be reduced, and at the same time, a stable BVO photoanode with high photoelectrocatalytic performance can be obtained.
[0021] Further, in step (2), the mixture is allowed to stand for 10-30 minutes.
[0022] Further, in step (3), CoMoO 4 The precursor solution was prepared by the following method: 4 ) 6 Mo 7 O 2 ·4H 2 O and CoCl 2 6H 2 O was mixed and dissolved in deionized water, sodium dodecyl sulfate was added, stirred, and then hydrothermally reacted to obtain CoMoO 4 Precursor solution.
[0023] Further, (NH 4 ) 6 Mo 7 O 2 ·4H 2 O、CoCl 2 6H 2 O. The mass volume ratio of sodium dodecyl sulfate and deionized water is 0.03-0.04 g: 0.002-0.006 g: 0.1-0.5 g: 65-75 mL.
[0024] Further, (NH 4 ) 6 Mo 7 O 2 ·4H 2 O、CoCl 2 6H 2 O. The mass volume ratio of sodium dodecyl sulfate and deionized water is 0.036 g: 0.004 g: 0.3 g: 70 mL.
[0025] Furthermore, in step (3), the hydrothermal reaction is carried out at 140-180° C. for 10-15 hours.
[0026] The beneficial effect of adopting the above further technical solution is that the overall photoelectrochemical performance of the CMO / SO / BVO photoanode can be significantly improved by adopting the above hydrothermal reaction temperature.
[0027] Furthermore, in step (3), calcination is performed at 350-450° C. for 1.5-2.5 h.
[0028] The present invention also provides a CMO / SO / BVO photoanode prepared by the method.
[0029] The present invention also provides application of the CMO / SO / BVO photoanode in preparing a photoelectrochemical cell.
[0030] The present invention has the following beneficial effects:
[0031] 1. Ternary metal oxide ABO 4 (A or B = Ni, Co, Mn, Mo, etc.) Due to the coexistence of two metal ions, the synergistic effect between the elements and the coupling effect between different metal ions are more conducive to the catalytic effect, better conductivity than other binary transition metal oxides, and can provide more reactive sites. As a typical transition metal oxide, cobalt molybdate (CoMoO 4 ) has become one of the most promising photoanode candidate materials due to its excellent electrochemical performance due to the complementarity and synergistic effect of Co and Mo in redox reactions. 4 With BiVO 4 Coupling to form photoanode materials for photoelectrochemical water splitting is an effective way to overcome the poor quantum yield caused by the rapid recombination of photogenerated electrons and holes. The close contact interface of the binary photoanode is crucial to improve the separation of photogenerated electrons and holes and enhance the photoelectrocatalytic activity. However, due to the large differences in lattice structures between different materials, BiVO 4 With CoMoO 4 Direct contact may also lead to unwanted recombination of photogenerated carriers. 2 ) is a non-toxic and non-polluting material with low discharge potential, abundant supply, high theoretical capacity (1965mAh / g) and macroscopic quantum tunneling effect, and is widely used in the field of electrochemistry. 2 The photogenerated charge carrier separation behavior can be further improved by making exclusive contacts with designated components.
[0032] 2. The present invention deposits BVO photoanode on a conductive glass (FTO) substrate, and then deposits SiO by dipping method. 2 The middle layer is dried to obtain the SO / BVO photoanode; followed by a hydrothermal reaction to obtain CoMoO 4 / SiO 2 / BiVO 4 (abbreviated as CMO / SO / BVO) photoanode. The CMO / SO / BVO of the present invention exhibits a better photocurrent (6.63 mA / cm2) than the CMO / BVO photoanode at 1.23 V vs. RHE. 2 ), which is 1.52 times that of CMO / BVO photoanode, 2.2 times that of SO / BVO photoanode and 3.18 times that of BVO photoanode. The charge separation efficiency of CMO / SO / BVO of the present invention (92.54%) is significantly higher than that of BVO (30.56%). The improvement of the photoelectric performance of CMO / SO / BVO ternary photoanode can be attributed to the construction of a good electrode / electrolyte interface that promotes the effective separation of photogenerated electron-hole pairs.
[0033] 3. The preparation method of the present invention is simple, the raw materials are easily available, and the operability is strong. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The XRD diagrams of the photoanodes of Example 1 and Comparative Examples 1-3 are shown;
[0035] Figure 2 The SEM images of the photoanode of Example 1 and Comparative Example 1 are shown;
[0036] Figure 3 TEM and HRTEM images of the photoanode of Example 1;
[0037] Figure 4 TEM and HRTEM images of the photoanode of Comparative Example 1;
[0038] Figure 5 Bi 4f spectra of the photoanode of Example 1 and Comparative Example 1;
[0039] Figure 6 2p spectra of the photoanodes of Example 1 and Comparative Example 1;
[0040] Figure 7 The O1s spectra of the photoanode of Example 1 and Comparative Example 1;
[0041] Figure 8 The Si 2p spectra of the photoanodes of Example 1 and Comparative Example 1 are shown;
[0042] Fig. 9 Mo 3d spectra of the photoanode of Example 1 and Comparative Example 1;
[0043] Fig.10 The Co 2p spectra of the photoanode of Example 1 and Comparative Example 1;
[0044] Fig.11The LSV curves of Example 1 and Comparative Examples 1-3 under photoanode illumination;
[0045] Fig.12 The IPCE spectra of the photoanode of Example 1 and Comparative Examples 1-3 are shown;
[0046] Fig.13 ABPE curves of the photoanode of Example 1 and Comparative Examples 1-3;
[0047] Fig.14 The EIS curves of the photoanode of Example 1 and Comparative Examples 1-3 are shown;
[0048] Fig.15 The photoanode Na of Example 1 and Comparative Examples 1-3 2 SO 3 There is a LSV curve diagram;
[0049] Fig.16 Graph showing the charge injection efficiency of the photoanode of Example 1 and Comparative Examples 1-3;
[0050] Fig.17 These are the MS test graphs of the photoanodes of Example 1 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0051] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0052] Embodiment 1:
[0053] A CMO / SO / BVO photoanode, the preparation method of which comprises the following steps:
[0054] (1) Preparation of electrodeposition solution: Bi(NO 3 ) 3 ·5H 2 O was dissolved in KI solution, the pH value was adjusted to 1.7, and then ethanol solution of p-benzoquinone was added and mixed to prepare an electrodeposition solution; wherein the concentration of KI solution was 0.4 mol / L, the concentration of p-benzoquinone ethanol solution was 0.23 mol / L, and Bi(NO 3 ) 3 ·5H 2 The molar volume ratio of O, KI solution and ethanol solution of p-benzoquinone is 0.04mol:50mL:20mL;
[0055] The electrodeposition of BiOI film was carried out in a three-electrode system, the counter electrode was a platinum electrode, the reference electrode was a silver-silver chloride electrode, and the working electrode was a cleaned FTO glass. The electrodeposition was carried out using a constant potential deposition method. The electrodeposition conditions were: the deposition voltage was -0.1V vs. Ag / AgCl, the deposition time was 300s, and the BiOI film was electrodeposited on the substrate material, which was rinsed with deionized water and dried, and then a 0.2 mol / L dimethyl sulfoxide solution of acetylacetonatovanadium was evenly drop-coated until the solution was evenly spread on the electrode surface, and then calcined at 450°C for 2h in a muffle furnace with a heating rate of 2°C / min, cooled to room temperature, and washed twice with a 1 mol / L NaOH solution until the surface V 2 O 5 was completely removed to obtain BiVO 4 Thin film, i.e. BVO electrode;
[0056] (2) The BVO electrode prepared in step (1) was placed in 10 mL of a NaOH solution of tetraethyl orthosilicate (concentration: 0.05 mol / L), and allowed to stand for 20 min. The electrode was taken out, washed with deionized water, and dried to obtain SiO 2 The middle layer, i.e., the SO / BVO electrode;
[0057] (3)CoMoO 4 Preparation of precursor solution: 0.036 g of (NH 4 ) 6 Mo 7 O 2 ·4H 2 O and 0.004 g CoCl 2 6H 2 O was mixed and dissolved in 70 mL of deionized water, 0.3 g of sodium dodecyl sulfate was added, and the mixture was stirred vigorously for 30 min at room temperature, and then hydrothermally reacted to obtain CoMoO 4 Precursor solution;
[0058] The SO / BVO electrode prepared in step (2) was placed on the CoMoO 4 The precursor solution was hydrothermally reacted at 160 °C for 12 h, washed with deionized water, placed in a muffle furnace, and calcined at 400 °C for 2 h to obtain CoMoO 4 / SiO 2 / BiVO 4 Photoanode, namely CMO / SO / BVO photoanode.
[0059] Embodiment 2:
[0060] A CMO / SO / BVO photoanode, the preparation method of which comprises the following steps:
[0061] (1) Preparation of electrodeposition solution: Bi(NO 3 ) 3 ·5H 2 O was dissolved in KI solution, the pH value was adjusted to 1, and then ethanol solution of p-benzoquinone was added and mixed to prepare an electrodeposition solution; wherein the concentration of KI solution was 0.3 mol / L, the concentration of p-benzoquinone ethanol solution was 0.2 mol / L, and Bi(NO 3 ) 3 ·5H 2 The molar volume ratio of O, KI solution and ethanol solution of p-benzoquinone is 0.02mol:45mL:18mL;
[0062] The electrodeposition of BiOI film was carried out in a three-electrode system, the counter electrode was a platinum electrode, the reference electrode was a silver-silver chloride electrode, and the working electrode was a cleaned FTO glass. The electrodeposition was carried out using a constant potential deposition method. The electrodeposition conditions were: the deposition voltage was -0.1V vs. Ag / AgCl, the deposition time was 300s, and the BiOI film was electrodeposited on the substrate material, which was rinsed with deionized water and dried, and then a 0.1 mol / L dimethyl sulfoxide solution of acetylacetonato vanadium was evenly drop-coated until the solution was evenly spread on the electrode surface, and then calcined at 400°C for 2.5h in a muffle furnace with a heating rate of 1.5°C / min, cooled to room temperature, and washed twice with a 0.8 mol / L NaOH solution until the surface V 2 O 5 was completely removed to obtain BiVO 4 Thin film, i.e. BVO electrode;
[0063] (2) The BVO electrode prepared in step (1) was placed in 10 mL of a NaOH solution of tetraethyl orthosilicate (concentration: 0.03 mol / L), and allowed to stand for 10 min. The electrode was taken out, washed with deionized water, and dried to obtain SiO 2 The middle layer, i.e., the SO / BVO electrode;
[0064] (3)CoMoO 4 Preparation of precursor solution: 0.03 g of (NH 4 ) 6 Mo 7 O 2 ·4H 2 O and 0.002 g CoCl 2 6H 2 O was mixed and dissolved in 65 mL of deionized water, 0.1 g of sodium dodecyl sulfate was added, and the mixture was stirred vigorously for 30 min at room temperature, and then hydrothermally reacted to obtain CoMoO 4 Precursor solution;
[0065] The SO / BVO electrode prepared in step (2) was placed on the CoMoO 4 The precursor solution was hydrothermally reacted at 140 °C for 15 h, washed with deionized water, placed in a muffle furnace, and calcined at 350 °C for 2.5 h to obtain CoMoO 4 / SiO 2 / BiVO 4 Photoanode, namely CMO / SO / BVO photoanode.
[0066] Embodiment 3:
[0067] A CMO / SO / BVO photoanode, the preparation method of which comprises the following steps:
[0068] (1) Preparation of electrodeposition solution: Bi(NO 3 ) 3 ·5H 2 O was dissolved in KI solution, the pH value was adjusted to 2, and then ethanol solution of p-benzoquinone was added and mixed to prepare an electrodeposition solution; wherein the concentration of KI solution was 0.5 mol / L, the concentration of p-benzoquinone ethanol solution was 0.3 mol / L, and Bi(NO 3 ) 3 ·5H 2 The molar volume ratio of O, KI solution and ethanol solution of p-benzoquinone is 0.06mol:55mL:22mL;
[0069] The electrodeposition of BiOI film was carried out in a three-electrode system, the counter electrode was a platinum electrode, the reference electrode was a silver-silver chloride electrode, and the working electrode was a cleaned FTO glass. The electrodeposition was carried out using a constant potential deposition method. The electrodeposition conditions were: the deposition voltage was -0.1V vs. Ag / AgCl, the deposition time was 300s, and the BiOI film was electrodeposited on the substrate material, which was rinsed with deionized water and dried, and then a 0.3 mol / L dimethyl sulfoxide solution of acetylacetonato vanadium was evenly drop-coated until the solution was evenly spread on the electrode surface, and then calcined at 500°C for 1.5h in a muffle furnace with a heating rate of 2.5°C / min, cooled to room temperature, and washed twice with a 1.2 mol / L NaOH solution until the surface V 2 O 5 was completely removed to obtain BiVO 4 Thin film, i.e. BVO electrode;
[0070] (2) The BVO electrode prepared in step (1) was placed in 10 mL of a NaOH solution of tetraethyl orthosilicate (concentration: 0.07 mol / L), and allowed to stand for 30 min. The electrode was taken out, washed with deionized water, and dried to obtain SiO 2 The middle layer, i.e., the SO / BVO electrode;
[0071] (3)CoMoO 4 Preparation of precursor solution: 0.04 g of (NH 4 ) 6 Mo 7 O 2 ·4H 2 O and 0.006 g CoCl 2 6H 2 O was mixed and dissolved in 75 mL of deionized water, 0.5 g of sodium dodecyl sulfate was added, and the mixture was stirred vigorously for 30 min at room temperature, and then hydrothermally reacted to obtain CoMoO 4 Precursor solution;
[0072] The SO / BVO electrode prepared in step (2) was placed on the CoMoO 4 The precursor solution was hydrothermally reacted at 180 °C for 10 h, washed with deionized water, placed in a muffle furnace, and calcined at 450 °C for 1.5 h to obtain CoMoO 4 / SiO 2 / BiVO 4 Photoanode, namely CMO / SO / BVO photoanode.
[0073] Comparative Example 1:
[0074] A CMO / BVO photoanode, the preparation method of which comprises the following steps:
[0075] The process is the same as Example 1 except that step (2) is not included.
[0076] Comparative Example 2:
[0077] A SO / BVO photoanode, the preparation method of which comprises the following steps:
[0078] The process is the same as Example 1 except that step (3) is not included.
[0079] Comparative Example 3:
[0080] A BVO photoanode, the preparation method of which comprises the following steps:
[0081] The steps (2) to (3) are not included, and the rest are the same as in Example 1.
[0082] Test example
[0083] In the following test examples, the XRD characterization of the samples was carried out on an Empyrean X-ray diffractometer of PANalytical, the Netherlands. The surface morphology of the samples was tested using an S-4800 field emission scanning electron microscope (SEM) with an acceleration voltage of 5 kV produced by Hitachi. The morphology and lattice spacing of the catalyst grains were observed and measured using a JEM-2100F transmission electron microscope (TEM) with an acceleration voltage of 300 kV produced by Hitachi. The types of elements contained in the catalyst samples and the chemical valence states corresponding to the elements were characterized using an X-ray photoelectron spectrometer from Shimadzu Corporation, Japan, and all binding energies were calibrated using the C1s peak at 284.8 eV as the standard.
[0084] Photoelectrochemical detection was performed using a Shanghai Chenhua CHl 760e electrochemical workstation and a standard three-electrode system for photoelectrochemical testing. The photoelectrochemical test was carried out in an electrochemical cell with an integrated three-electrode system with a quartz window, which mainly includes a working electrode, a reference electrode, and a counter electrode. Among them, a platinum sheet electrode (1cm×l cm) was used as a counter electrode, Ag / AgCl was used as a reference electrode, and the prepared photoanode (1cm×2cm) was used as a working electrode. 1M potassium borate buffer (PH=9.5) was used as the electrolyte. A solar simulator was used as the light source for the PEC test, and the illumination intensity was adjusted to 1 sun (100MW / cm 2 ). The linear sweep voltammetry method was used to plot the photocurrent density curve under illumination. The potential was scanned in the negative direction at a rate of 50mV / s and all photocurrent data were recorded. The charge transfer efficiency of the prepared photoanode was evaluated and analyzed by electrochemical impedance spectroscopy under illumination, and the test results were analyzed by equivalent circuit fitting using ZView software. Under dark conditions and an AC amplitude of 15mV, Mott-Schottky experimental data of the photoanode with a measurement frequency of 1kHz were collected. If the Faraday efficiency of the photoanode is 100%, the bias-assisted photoelectric conversion efficiency can be directly calculated based on the LSV curve. The incident photon-electron conversion efficiency is usually called the action spectrum of the photocurrent, which is the response relationship between the photocurrent and the wavelength under the wavelength of monochromatic light, and describes the quantum efficiency at different wavelengths. During the IPCE test, the response data of the current and the wavelength of monochromatic light were recorded under an external bias of 1.23V vs.RHE.
[0085] 1. XRD test was performed on the photoanodes prepared in Example 1 and Comparative Examples 1-3. The results are shown in Figure 1 .
[0086] Depend on Figure 1It can be seen that the diffraction peak position of BVO prepared by electrochemical deposition method in Comparative Example 3 coincides with the peak position of the standard card JCPDS no.14-0688 of BVO, indicating that the synthesized BVO photoanode has a monoclinic crystal structure. Carefully comparing the diffraction peak positions of CMO / SO / BVO prepared in Example 1, CMO / BVO prepared in Comparative Example 1, SO / BVO prepared in Comparative Example 2, and BVO photoanode prepared in Comparative Example 3, it can be found that all peak positions coincide well, and no impurity peaks are found, indicating that the treatment of SO and CMO does not change the crystal structure of BVO.
[0087] 2. The photoanodes prepared in Example 1 and Comparative Examples 1-3 were subjected to SEM examination. The results are shown in Figure 2 ( Figure 2 In the figure, a is BVO photoanode, b is CMO / SO / BVO photoanode, c is CMO / BVO photoanode, and d is SO / BVO photoanode).
[0088] Depend on Figure 2 It can be seen that the BVO photoanode prepared in Comparative Example 3 is constructed of some irregular worm-like nanoparticles with a particle size of about 200 nm. The SEM images of the CMO / SO / BVO photoanode prepared in Example 1, the CMO / BVO photoanode prepared in Comparative Example 1, and the SO / BVO photoanode prepared in Comparative Example 2 show that SO and CMO are loaded onto the BVO photoanode without changing the nanopore structure of the BVO photoanode.
[0089] 3. The photoanodes prepared in Example 1 and Comparative Example 1 were subjected to TEM and HRTEM tests. The results are shown in Figure 3-Figure 4 ( Figure 3 a is TEM, b and c are HRTEM, and di is TEM-EDS; Figure 4 same Figure 3 ).
[0090] Figure 3 A and Figure 4 Figure a further confirms the worm-like structure of BVO, which is well corroborated with the SEM observation results.
[0091] Figure 3 In bc and Figure 4 In bc, the lattice spacing of the CMO / SO / BVO photoanode prepared in Example 1 and the CMO / BVO photoanode prepared in Comparative Example 1 by high resolution transmission electron microscopy (HRTEM) is 0.31 nm, which corresponds to the (-121) crystal plane of BVO (JCPDS No.14-0688).
[0092] Figure 3 Medium b and Figure 4It can be seen intuitively in b that the surface of the BVO photoanode is tightly and evenly covered by an ultra-thin and amorphous CMO / SO composite layer and a CMO layer, respectively. This observation not only reinforces the successful synthesis results of Example 1 CMO / SO / BVO photoanode and Comparative Example 1 CMO / BVO photoanode, but also further reveals its complex hierarchical structural characteristics.
[0093] Figure 3 Zhongdi and Figure 4 It can be seen that compared with the CMO / BVO photoanode, the TEM-EDS of the CMO / SO / BVO photoanode confirms the presence of the Si element, which strongly proves that the SiO2 intermediate layer was successfully introduced without affecting the original structure of the CMO / BVO photoanode.
[0094] 4. The elemental composition and bonding environment of the photoanode prepared in Example 1 and Comparative Example 1 were tested by XPS. The results are shown in Figure 5-Figure 10 .
[0095] Depend on Figure 5-6 It can be seen that the peaks at 159.1 and 164.4 eV correspond to Bi 4f 7 / 2 and Bi 4f 5 / 2 , the peaks at 516.7 eV and 524.1 eV correspond to V 2p 3 / 2 and V 2p 1 / 2 , indicating that Bi and V elements only exist in BiVO 4 This is a chemical environment bond.
[0096] Figure 7 The positions of three fitting peaks are shown. The peaks at 529.9 eV, 530.9 eV and 534.3 eV are characteristic peaks of oxygen in the lattice, adsorbed hydroxyl groups and chemically adsorbed or dissociated oxygen in water molecules, respectively. The peak area at 530.9 eV in the CMO / SO / BVO photoanode is significantly higher than the peak height at the CMO / BVO photoanode, which is attributed to the SiO 2 Oxygen atoms in the crystal lattice.
[0097] Figure 8 In the CMO / SO / BVO sample, a peak at 104.4 eV attributed to SiO 2 The peak near 99.7 eV corresponds to the Si present due to insufficient oxidation during low temperature annealing.
[0098] Fig. 9 In all samples, binding energy peaks at 231.6 and 234.7 eV were observed, which are attributed to Mo3d 5 / 2 and Mo 3d 3 / 2 existence.
[0099] Fig.10 The chemical state of the CMO capping layer is revealed, and the peaks at 777.9 and 794.4 eV correspond to the Co 2p 3 / 2 and Co 2p 1 / 2 The XPS test results further verified the successful preparation of the CMO / SO / BVO photoanode.
[0100] 5. In order to evaluate the photoelectrochemical performance of all photoanodes, the photocurrent of the photoanodes prepared in Example 1 and Comparative Examples 1-3 was tested by linear sweep voltammetry (LSV). Fig.11 .
[0101] Depend on Fig.11 It can be seen that the BVO prepared in comparative example 3 exhibits a lower photocurrent density response. When the bias voltage is 1.23 V vs. RHE, the photocurrent density is 2.08 mA / cm 2 .
[0102] After SO was loaded on the BVO film, the SO / BVO prepared in Comparative Example 2 showed an enhanced photocurrent density. Among them, the photocurrent density of SO / BVO was the highest, and the photocurrent could reach 3.01 mA / cm at a bias of 1.23 V vs. RHE. 2 , which is 1.45 times that of BVO photoanode.
[0103] After loading CMO, the photocurrent density of the CMO / SO / BVO photoanode prepared in Example 1 is much higher than that of BVO and SO / BVO, and its photocurrent density at 1.23 V vs. RHE reaches a maximum value of 6.63 mA / cm 2 , which is 3.18 times that of the BVO photoanode, proving that the construction of the ternary CMO / SO / BVO photoanode has significant advantages in enhancing the PEC performance.
[0104] Compared with the CMO / BVO prepared in comparative example 1, the photocurrent at 1.23V vs. RHE reached 4.35mA / cm 2 , which is 2.09 times that of the BVO photoanode, and the starting potential is negatively shifted, indicating that the water oxidation driving potential of the CMO / BVO photoanode is low. The introduction of CMO can promote the water oxidation reaction at the interface between the photoanode and the electrolyte, which may provide a more favorable pathway for the rapid participation of charges in the oxygen evolution process. The above results show that the construction of the CMO / SO / BVO photoanode can further promote the transfer of photogenerated electrons and holes, accelerate the kinetics of the water oxidation reaction and inhibit the recombination of carriers.
[0105] VI. In order to prove that the photoanode can effectively convert the absorbed photons into current, the photoanode prepared in Example 1 and Comparative Examples 1-3 was subjected to IPCE characterization test. Fig.12 .
[0106] Depend on Fig.12 It can be seen that all samples show the maximum photoelectric conversion efficiency at 400nm, because the light energy at a wavelength of 400nm excites more photogenerated carriers. The IPCE value of the CMO / SO / BVO photoanode prepared in Example 1 at a wavelength of 430nm can reach 80%, which is better than CMO / BVO (66%), SO / BVO (42%) and BVO (41%) photoanodes. Therefore, the above observations show that the increased photocurrent density is not due to the expansion of the light absorption range, but due to the increase in IPCE.
[0107] VII. The solar energy to hydrogen conversion efficiency of the half-cell photoanode was evaluated by calculating the ABPE of the photoanode prepared in Example 1 and Comparative Examples 1-3. Fig.13 .
[0108] Depend on Fig.13 It can be seen that the photoelectric conversion efficiency of the CMO / SO / BVO photoanode prepared in Example 1 is significantly better than that of CMO / BVO, SO / BVO and BVO photoanodes under the same external bias voltage, showing relatively excellent photoelectrochemical water splitting performance. At 0.75V vs. RHE, the CMO / SO / BVO photoanode has the largest ABPE value of about 1.92%, indicating that the CMO / SO / BVO photoanode can achieve extremely high photocurrent density at a relatively small bias voltage.
[0109] 8. In order to explore the properties of charge transport between the photoanode and the electrolyte solution interface, the photoanode prepared in Example 1 and Comparative Examples 1-3 was tested for electrochemical impedance. Fig.14 .
[0110] Depend on Fig.14 It can be seen that the smaller the semicircle radius of the photoanode material, the smaller the transfer resistance of the material. The CMO / BVO photoanode has a smaller arc radius than the untreated BVO, proving that the introduction of CMO improves the conductivity of the BVO photoanode and accelerates the charge transfer at the solid-liquid interface.
[0111] 9. In the presence of 0.5M Na 2 SO 3 The LSV curves of the photoanodes prepared in Example 1 and Comparative Examples 1-3 were measured in 1M KBi (pH = 9.5) as a hole scavenger. Fig.15 .
[0112] Depend on Fig.15It can be seen that compared with the test results without adding hole sacrificial agent, the photocurrent density of BVO has been greatly improved, confirming that there is a serious recombination of photogenerated electron-hole pairs inside BVO and at the interface between the photoanode and the electrolyte solution. 2 SO 3 The photocurrent density is significantly improved compared with that of BVO, which means that the composite photoanode can effectively inhibit the serious recombination of photogenerated electron-hole pairs in the BVO photoanode and promote the separation and transfer of electrons and holes.
[0113] Hole injection efficiency is an important parameter for evaluating the proportion of carriers actually participating in the redox reaction at the electrode surface / electrolyte interface. It is calculated using the following formula: is the photocurrent generated by water oxidation of the electrode in 1M KBi solution; For electrodes containing 0.5 M Na 2 SO 3 Photocurrent generated by water oxidation in 1M KBi solution as hole scavenger. Results are shown in Fig.16 .
[0114] Depend on Fig.16 It can be seen that at 1.23V vs. RHE, the hole injection efficiency of the SO / BVO composite photoanode reaches 43.18%, which is not much different from the 30.56% of the BVO photoanode, indicating that the introduction of SO will not change the kinetic process of water reaction on the surface of the SO / BVO composite photoanode. The surface hole injection efficiency of the CMO / BVO photoanode is 63.32%, which confirms that CMO plays the role of a co-catalyst, reduces the reaction barrier between the semiconductor and the electrolyte, and improves the kinetic process between the photoanode and the electrolyte. In contrast, the surface hole injection efficiency of CMO / SO / BVO (92.54%) is better than that of CMO / BVO, which is consistent with the property that the ternary structure can enhance charge transfer.
[0115] 10. To study the photogenerated carrier transfer characteristics and the effect on the photoelectrocatalytic activity of the photoanode prepared in Example 1 and Comparative Examples 1-3, a Mott-Schottky (MS) curve test was performed under dark conditions. The results are shown in FIG. Fig.17 .
[0116] Depend on Fig.17 It can be seen that the three photoanodes all show a positive slope on the MS curve, reflecting that electrons are the main carriers. Since the semiconductor carrier concentration is inversely proportional to the slope of the MS curve, this means that the CMO / SO / BVO photoanode has the highest donor concentration, mainly due to the internal structure of the ternary photoanode accelerating the effective separation and transfer between electrons and holes.
[0117] The present invention further improves the photogenerated carrier separation behavior by introducing SO into the CMO / BVO photoanode, significantly improving the PEC water splitting effect. When the bias voltage is 1.23V vs. RHE, the prepared CMO / SO / BVO photoanode achieves 6.63mA / cm 2 , better than CMO / BVO (4.35mA / cm 2 )、SO / BVO(3.01mA / cm 2 ) and BVO (2.08 mA / cm 2 The efficient PEC water splitting performance of the ternary CMO / SO / BVO photoanode is attributed to the reduced reaction barrier between the semiconductor and the electrolyte, which in turn improves the kinetics between the photoanode and the electrolyte.
[0118] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a CMO / SO / BVO photoanode, characterized in that: The following steps are included in sequence: (1) Electrodepositing a BiOI film on a substrate, cleaning and drying, then drop-coating a dimethyl sulfoxide solution of vanadium acetylacetonate, calcining, cooling, and secondary cleaning to obtain a BiVO4 film, i.e., a BVO electrode; (2) placing the BVO electrode obtained in step (1) in a NaOH solution of tetraethyl orthosilicate, allowing to stand, washing, and drying to obtain a SiO2 intermediate layer, i.e., a SO / BVO electrode; (3) placing the SO / BVO electrode prepared in step (2) in a CoMoO4 precursor solution, subjecting it to a hydrothermal reaction, washing it, and calcining it to obtain a CoMoO4 / SiO2 / BiVO4 photoanode, i.e., a CMO / SO / BVO photoanode.
2. The method for preparing the CMO / SO / BVO photoanode according to claim 1, characterized in that: In step (1), the electrodeposition solution for electrodepositing the BiOI film is prepared by the following method: dissolving Bi(NO3)3·5H2O in a KI solution, adjusting the pH value to 1-2, and then adding an ethanol solution of p-benzoquinone and mixing to prepare an electrodeposition solution.
3. The method for preparing the CMO / SO / BVO photoanode according to claim 1, characterized in that: In step (1), calcination is performed at 400-500° C. for 1.5-2.5 h.
4. The method for preparing the CMO / SO / BVO photoanode according to claim 1, characterized in that: In step (2), the concentration of the NaOH solution of tetraethyl orthosilicate is 0.03-0.07 mol / L.
5. The method for preparing the CMO / SO / BVO photoanode according to claim 1, characterized in that: In step (2), let stand for 10-30 minutes.
6. The method for preparing the CMO / SO / BVO photoanode according to claim 1, characterized in that: In step (3), the CoMoO4 precursor solution is prepared by the following method: (NH4)6Mo7O2·4H2O and CoCl2·6H2O are mixed and dissolved in deionized water, sodium dodecyl sulfate is added, stirred, and then hydrothermally reacted to obtain a CoMoO4 precursor solution.
7. The method for preparing a CMO / SO / BVO photoanode according to claim 1, characterized in that: In step (3), the hydrothermal reaction is carried out at 140-180° C. for 10-15 h.
8. The method for preparing a CMO / SO / BVO photoanode according to claim 1, characterized in that: In step (3), calcination is performed at 350-450° C. for 1.5-2.5 h.
9. A CMO / SO / BVO photoanode, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.
10. Use of the CMO / SO / BVO photoanode according to claim 9 in the preparation of photoelectrochemical cells.
Citation Information
Cited By
CoMoO4 / BiVO4 nano material, preparation method and application
CN120189951A
Bi2O2S / N-BiVO4 photo-anode as well as preparation method and application thereof
CN121554055A
Bi2o2s / n-biVO4 photoanode and preparation method and application thereof
CN121554055B